2005
DOI: 10.1212/01.wnl.0000191565.11065.11
|View full text |Cite
|
Sign up to set email alerts
|

Visual dysfunction in Parkinson disease without dementia

Abstract: Patients with mild to moderate Parkinson disease showed impaired visual perception and cognition compared with elderly control subjects. Visual dysfunction contributes to parkinsonian disability through its influences on cognition and locomotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
223
3
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(248 citation statements)
references
References 48 publications
15
223
3
7
Order By: Relevance
“…In a study of patients with schizophrenia, Slaghuis (1998) found that patients diagnosed with schizophrenia were impaired for moving and stationary gratings, with most consistent deficits at higher spatial frequencies. Unlike the present HD sample, patients diagnosed with Parkinson's disease (Uc et al, 2005) and schizophrenia (O'Donnell et al, 2006) can show dot motion deficits as well as impaired stationary contrast sensitivity. Thus, in Parkinson's disease, aging, and schizophrenia, the pattern of visual deficits frequently differs from that of HD gene carriers.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…In a study of patients with schizophrenia, Slaghuis (1998) found that patients diagnosed with schizophrenia were impaired for moving and stationary gratings, with most consistent deficits at higher spatial frequencies. Unlike the present HD sample, patients diagnosed with Parkinson's disease (Uc et al, 2005) and schizophrenia (O'Donnell et al, 2006) can show dot motion deficits as well as impaired stationary contrast sensitivity. Thus, in Parkinson's disease, aging, and schizophrenia, the pattern of visual deficits frequently differs from that of HD gene carriers.…”
Section: Discussioncontrasting
confidence: 64%
“…Visual perceptual impairments have been reported in other neurodegenerative disorders. For example, patients with Parkinson's disease show deficits on tests of contrast sensitivity (Rodnitzky, 1998;Uc et al, 2005), color vision (Rodnitzky, 1998), and motion perception (Uc et al, 2005). In Alzheimer's disease, deficits in contrast sensitivity (Gilmore et al, 2005;Rizzo et al, 2002) and motion perception (Rizzo et al, 2002) have been described.…”
Section: Introductionmentioning
confidence: 99%
“…The CRAF test might help identify patients who have visual perception problems and are at risk of falls and will allow us to tailor a rehabilitation program accordingly. The exact etiology of visual dysfunction in PD is not fully understood; it may be related to retinal dopamine deficiency or higher order visual cortical dysfunction [12,23].…”
Section: Discussionmentioning
confidence: 99%
“…The increased visual dependence may also limit a patient's ability to compensate fully for gait disorders, particularly in situations involving sensory conflict caused by excessive visual motion [11]. Further studies suggest that visual dysfunction may also contribute to PD disability through influences on cognition and locomotion [12]. A better understanding of these events and their interrelationships will provide the underpinning for efforts to improve rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…9,[43][44][45] Visual perception and cognition abnormalities are associated with dysfunction ranging from retinal to cortical levels. 17 Visual dysfunction is associated with gait and balance impairment, and visual cues can improve freezing of gait.…”
Section: Visionmentioning
confidence: 99%